Risk Factors for Postpartum Depression During COVID-19 Pandemic: A Systematic Literature Review. (December 2021) - Usmani, Sadia; Greca, Elona; Javed, Sana; Sharath, Medha; Sarfraz, Zouina; Sarfraz, Azza; Salari, Syeda Wajiha; Hussaini, Syed Sameer; Mohammadi, Asma; Chellapuram, Nikitha; Cabrera, Erik; Ferrer, Gerardo
Introduction: The COVID-19 pandemic has had a devastating worldwide effect on mental health. Recent studies correlate the spreading of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with symptoms of depression, most prominent in postpartum women. Our systematic literature review scope is to identify the risk factors and predictors for postpartum depression (PPD) and describe the steps that should be taken to help postpartum women. This study will help clinicians, researchers, and policymakers to elucidate the predictors of PPD during this pandemic and prevent these adverse outcomes in future crises. Methods: We conducted a systematic search by employing databases PubMed, Google Scholar, Scopus, and Embase to identify articles published before March 2021. About 463 publications were generated during our search process and from those, 36 were reviewed, summarized, and synthesized. Studies qualified the criteria if they (1) utilized qualitative or quantitative design, (2) explored the risk factors for PPD, and (3) were written in English. Quality evaluation of each study was achieved by using criteria set by Lincoln and Guba. Results: Prevalence of depression symptoms ranged from 7% to 80.8% in postpartum women during the SARS-COV 2 pandemic. The risk factors for PPD were classified into 6 major categories: socio-demographic, psychological, pre-existing pathology, metabolic factors, previous events of miscarriage, and media misinformation. Conclusion: It is extremely vital to care for women's mental health during pregnancy and after childbirth during these unprecedented times. This review urges the need to design adequate interventions for this vulnerable population to prevent negative consequences of PPD.